(untitled) (Revista Contexto & Educação, 2023)
This text is the result of a research carried out with the aim of analyzing how the advances of neuroscience have been considered in the educational field, with its possibilities and limitations, understanding that both exist. For that, the question is: what does the brazilian research developed in the field of Education about Neuroscience reveal? The goal is to review the national research identifying features of these investigations, specially the way how emotions, motivation, attention, executive functions, memory and brain plasticity are presented in brazilian thesis and dissertations. In methodological terms the study is qualitative, bibliographic and the “state of knowledge” kind, identifying 10 thesis and 28 dissertations as focus of the investigation. The analysis of these studies identify features such as: people and groups interested in the theme; context of the investigation present in the studies; and the presence of conditioners investigated in Education research. The results point out a growth in research in the last three years, although it is noticeable the need to improve the articulation between Neuroscience and Education, especially in educational practice.